New perspectives of future criminalistics (Academic Journal of Internal Affairs, 2019)
The 21st Century innovation trends have reached forensic science, too and new devices for law enforcement appear every day. The changing of this phenomena raises many questions. How reliable are the new devices? Do they replace previous methods, technical background? Do we need further improvements, or do we need to adapt the present ones for the challenges of crime investigation? Dogs have been used for many centuries for several purposes by mankind, including tracking methods. Do we need to develop artificial noses, analytical instruments to match the trends? This study tries to answer these questions, supported by upto- date knowledge.
Keywords: criminalistics; police dog; forensic odorology; innovation